PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP KEMAMPUAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 1 PANTI - Ricci Gemarni Tatalia, M.Pd (Universitas PGRI Sumatera Barat, 2017)
This study was generated from the problem of students’ ability in writing news texts ini class VIII, SMPN 1 Panti. Some of the problem were (1) lack of the students’ response towards news writing teaching and learning process, (2) lack of teacher’s creativity in designing interesting news sriting learning model, (3) no appropriate creative techniques applied by the teacher which could train the students to develop their skill in writing news texts and (4) lack of the students’ motivation in participating in teaching and learning process because of their lack of understanding in the elements of news. Thus, this study was aimed at escribing the effect of the students’ ability ini writing news texts in class VIII SMP N 1 Panti. This was a quantitative research with factorial 2x2 experimental design. The population was the students in class VIII SMPN 1 Panti. Sampling technique was done by using random sampling and the data was collected through test. The result of the study revealed that cooperative learning model with STAD mind mapping type affected the students’ ability in writing news texts